Temporal changes of land use in Asi river delta (Hatay, Southern Turkey) - Korkmaz, Huseyin; Cetin, Bayram; Kuscu, Veysel; Ege, Ismail; Bom, Ahmet; Ozsahin, Emre; Karatas, Atilla (Triveni Enterprises, 2012)
Increasing non-ecological land use necessitates more efficient using and utilization of land by man. Therefore, in recent years studies on sustainable land use have gained momentum. In this study, temporal change in land use, mainly between years 1940 and 2010, in Asi river delta on Southern Turkey was covered. To this end, in addition to literature, topographical maps and satellite images from year 1940 and after were used. Also, data were collected through field studies and interviews. Collected data were evaluated from geographical viewpoint using Geographical information system (GIS) and Remote sensing (RS) methods. Unplanned settlement in delta has reached levels high enough to threaten agricultural fields. Especially, great tendency shown by Samandag city and the villages around it towards expanding into delta is an indicator of this threat. In addition, uncontrolled sand mining and touristic facilities on the coastline are also indicators of wrong land use. In future, direction of settlement to slopes around the delta rather than lowlands will be a much more ecological approach.
Keywords: Land use; Geographical information systems (GIS); Remote sensing (RS); Asi river delta (Hatay, South Turkey)